2011
DOI: 10.1364/boe.2.002577
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation of rod photoreceptor reflectance in the human retina

Abstract: Using adaptive optics imaging tools to image the living retina, numerous investigators have reported temporal fluctuation in the reflectivity of individual cone photoreceptors. In addition, there is cone-to-cone (spatial) variation in reflectivity. As it has only recently become possible to image the complete rod photoreceptor mosaic in the living human retina, we sought to characterize the reflectivity of individual rods and compare their behavior to that of foveal/parafoveal cones. Across two subjects, we we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 34 publications
2
87
1
Order By: Relevance
“…To quantify this change and compare it to the values predicted by the SCE, the imaging was repeated with constant PMT gain. Despite the photoreceptor reflectance fluctuations [11,41,42] and other sources of variability such as image registration, tear film and subject alignment, the observed reflectance amplitude values (shown in Table 2 ) are consistent with the SCE predictions. Table 2 Measured relative average image intensities for images collected with constant PMT gain compared against predicted values (in parenthesis) according to the SCE measured objectively at fixation (ρ = 0.11 mm ) [43].…”
Section: Figsupporting
confidence: 76%
See 2 more Smart Citations
“…To quantify this change and compare it to the values predicted by the SCE, the imaging was repeated with constant PMT gain. Despite the photoreceptor reflectance fluctuations [11,41,42] and other sources of variability such as image registration, tear film and subject alignment, the observed reflectance amplitude values (shown in Table 2 ) are consistent with the SCE predictions. Table 2 Measured relative average image intensities for images collected with constant PMT gain compared against predicted values (in parenthesis) according to the SCE measured objectively at fixation (ρ = 0.11 mm ) [43].…”
Section: Figsupporting
confidence: 76%
“…annular) could be used to monitor the evolution of the multi-modal patterns, to determine if subtle transverse changes take place in the photoreceptor mosaic. This could be used to study the disc shedding and renewal process, in a similar way that the evolution of the fundamental modes has been used before [11,42,[50][51][52]. If the multi-modal intensity profiles are not affected by daily changes, they could potentially reveal early changes in photoreceptor disease such as swelling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their number and position, one of the most noticeable features of the photoreceptors is the spatial variability of their reflectance, which has been clearly detected with all AO imaging modalities [9][10][11][12][13][14][15][16][17][18]. From early observations, it has been shown that the cones change their reflectance with time even in healthy retinas [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the changes in reflectance occur independently between the cones [9] and that the cones change their brightness on time scales ranging from milliseconds [10,17] and seconds [11,15,16] to hours [9,12,13], days [14], months or years [18].…”
Section: Introductionmentioning
confidence: 99%